Analysis of Total Displacement Value in Mine Opening with and Without Supports in Weak Rock - Ira, Nurmaya Putri; Dwi Puteri, Martsa Farindi; Catherine, Liany Ayu (Fakultas Teknik Universitas Tanjungpura, 2025)
The stability of underground openings in weak rocks presents a major challenge in geotechnical engineering due to the time-dependent deformation and low mechanical strength of such materials. This study analyzes total displacement in tunnel structures with and without support systems, focusing on the Cileunyi